Association of Vitamin D receptor genetic variant Fok1, Bsm1, Apa1, and Taq1 polymorphism and Vitamin D deficiency with increased incidence of coronary artery disease - Mahaboob Vali Shaik; Swarna Deepak Kuragayala; S Madhuri; Munni Shaik; S BabuLal; Subrahmanyam Gangapatnam (Biomedical and Biotechnology Research Journal, 2023)
Background: Coronary artery disease (CAD), the leading cause of mortality globally. Very few studies on Vitamin D receptor (VDR) single-nucleotide polymorphisms in association with CAD were available. The current study explored the association between VDR regions Fok I (rs10735810), Bsm I (rs1544410), ApaI (rs7975232), and Taq I (rs731236) with CAD risk. Methods: A study was conducted on 100 patients with CAD along with control subjects without CAD. Correlation assessed between 1,25-dihydroxy Vitamin D levels and VDR gene polymorphism. Results: The frequency of Genotype Bb was increased (13%) in co-dominant (odds ratio [OR]: 1.95; confidence interval [CI]: 0.96–4.0; P = 0.004) and over-dominant (OR: 2.4; CI: 1.25–4.6; P = 0.0075) models in cases than compared to control. Genotype Aa was increased (13%) in co-dominant (OR: 2.29; CI: 1.3–3.98, P = 0.003) and in over-dominant (OR: 1.72; CI: 1.0–2.8, P = 0.03) models. The genotype ff was decreased (11.5%) in co-dominant (OR: 0.18; CI: 0.07–0.48, P = 0.0008) and recessive models (OR: 0.15; CI: 0.08–0.5, P = 0.0003) in cases. VDR Genotypes such as Aa + aa (21%), BB + Bb (14%), Aa (13%), Bb (13%), FF + Ff (12%), Tt + tt (8%), aa (8%), Ff (8%), and tt (8%) were responsible for higher CAD risk. Alleles a (14%), B (8%), and t (8%) lead to higher CAD risk. Serum Vitamin-D levels were lower in “Aa,” Aa + aa, and BB + Bb genotypes, while higher in aa, tt, Tt + tt, bb, FF + Ff and Ff, and Ff genotypes of VDR. Conclusions: Significant association observed between serum Vitamin D levels and Aa + aa of APA 1, Tt + tt of VDR gene (P < 0.001). Deficiency of 1, 25-dihydroxy Vitamin D and the prevalence of APA I, BsmI, Taq1, Fok I polymorphisms are important risk markers for CAD.